Mad men. Season two [videorecording (DVD)] - Weiner, Matthew; Hamm, Jon, 1971-; Slattery, John, 1962-; Moss, Elisabeth, 1982-; Jones, January, 1978-; Kartheiser, Vincent, 1979- (Lions Gate Films, 2009)
Returning for its second season, the Golden Globe winning series for Best TV Drama continues to blur the lines between truth and lies, perception and reality. Moving in a new direction, can Sterling Cooper keep up? Meanwhile, the private life of Don Draper becomes complicated in a new way. What is the cost of his secret identity?